Utilization of Characteristic Contrast Between Corduroy and Leather Materials in the Design of Women's Flat Shoes - Kallia Amala Sagwiangsa (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The use of textile materials in footwear construction has evolved through various material combinations to enhance product functionality and comfort. However, textile materials with distinctive textural characteristics such as corduroy remain predominantly applied in apparel and are rarely found in functional footwear construction. This study aims to explore the potential of corduroy by utilizing its inherent flexibility and suppleness within shoe construction systems while preserving its original properties, rather than merely serving as a decorative surface element. Through a Research Through Design approach focused on design innovation and knowledge preservation, this research conducted material characteristic studies, iterative sketching and mock-up exploration, and prototyping to develop women's flat shoes combining leather and corduroy. A market comparative analysis of 81 footwear products revealed that 60.5 percent of existing leather-corduroy combinations only utilize corduroy as a decorative element, while only 2.5 percent exploit corduroy's functional characteristics. The selected design maximizes material contrast: the rigidity of nubuck leather maintains structural integrity, while the flexibility of corduroy enables a foldable rear mechanism that offers two distinct wearing variations. Industrial practitioner consultation confirmed the design's feasibility and comfort. The resulting prototype demonstrates a high degree of novelty in both functional mechanism and visual configuration, contributing practical insights for footwear design development through the functional utilization of contrasting textile materials. Keyword: Corduroy, leather, material combination, flat shoes, design novelty